Thermostability and Photostability of Shrimp Waste Oil Based on Sun Protection Factor Value, Erythema Transmission, Pigmentation Transmission and Free Fatty Acid Content - Agustiawan, Deri; Rahmalia, Winda; Alimuddin, Andi Hairil; Prayitno, Dwi Imam; Sayekti, Endah (Universitas Diponegoro, 2024)
The high production of shrimp is accompanied by an increase in by-products (cephalothorax, carapace, and tail), which are discarded as waste. Therefore, a solution is needed to convert shrimp waste into economic value products like shrimp waste oil (SWO). SWO contains fatty acids and astaxanthin, which have antioxidant activity to scavenge free radicals, so it can prevent skin damage such as wrinkles and dryness. Due to its fatty acids and astaxanthin content, SWO can be applied as a sunscreen. However, heating and irradiation can degrade bioactive compounds that are beneficial for health. Thermostability and photostability tests are needed to determine the best storage conditions for SWO based on sun protector factor (SPF) values, erythema transmission (%Te), pigmentation transmission (%Tp), and free fatty acid (FFA) content. The yield of SWO obtained was 2.569% from 100 grams of dry shrimp waste weight. Analysis by using FTIR showed the presence of astaxanthin content in SWO, while GC-MS showed that the SWO contains up to 32.66% of hexanoic acid. SWO thermostability and photostability tests showed a decrease in SPF values and an increase in %Te and %Tp as heating and irradiation time increased. This is due to the photobleaching effect. There was no significant change in the FFA value, indicating that SWO is quite resistant to heating and irradiation.